Tiktok Shop Optimization Counseling for SMEs in Ulujami Village - Engga Jalaludin; Nur Majdina; Rizka Fajrina; Najela Safa Camilla; Ryan Rinaldi; Fawaz Fadillah (Jurnal Pengabdian Masyarakat (Bisma), 2023)
Abstract Tiktok is a social media platform for sharing short videos, but recently TikTok has launched a new feature, namely the TikTok Shop, this feature is a place where trade transactions occur and also brings sellers and buyers together like other e-commerce platforms. In this case, it is an opportunity for the public, especially sellers, to be able to reach consumers through this TikTok Shop and optimize their use based on the features in the existing TikTok Shop. But unfortunately, not all Indonesian people understand how to use the TikTok Shop. Therefore, through the Community Service Program which is accommodated in Darunnajah University, it is hoped that this will be a solution so that people can understand more about its use so that they can increase their business reach. This KKN program aims to educate the public about the advantages and disadvantages of the TikTok Shop, as well as its benefits and impact on their business. The KKN program was carried out in Ulujami Village, Pesanggrahan District, South Jakarta, DKI Jakarta. The method used is the introduction method and seminars.